2003
DOI: 10.1182/blood-2003-04-1291
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid as a novel source of mesenchymal stem cells for therapeutic transplantation

Abstract: Amniotic fluid as a novel source of mesenchymal stem cells for therapeutic transplantationHuman mesenchymal stem cells (MSCs) are multipotent stem cells, able to differentiate into multiple mesenchymal lineages. [1][2][3] Previously, we have shown that human fetal lung-derived MSCs enhance the engraftment of human umbilical cord blood (UCB)-derived CD34 ϩ hematopoietic cells in nonobese diabetic-severe combined immunodeficiency mice. 1 Here we show that secondtrimester amniotic fluid is an abundant source of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
264
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 684 publications
(273 citation statements)
references
References 8 publications
5
264
0
4
Order By: Relevance
“…After these treatments, AFCs gave rise to adipocytes and osteoblasts, when fibroblasts were the predominant cell population. In this regard, it has been reported [10,12,13] that amniotic fluid mesenchymal stem cells display a multilineage differentiation potential into fibroblasts, adipocytes and osteocytes. We suggest that the limited differentiation potential towards mesenchymal lineages that we found in our AFC cultures could be due to the cell heterogeneity with high percentage of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After these treatments, AFCs gave rise to adipocytes and osteoblasts, when fibroblasts were the predominant cell population. In this regard, it has been reported [10,12,13] that amniotic fluid mesenchymal stem cells display a multilineage differentiation potential into fibroblasts, adipocytes and osteocytes. We suggest that the limited differentiation potential towards mesenchymal lineages that we found in our AFC cultures could be due to the cell heterogeneity with high percentage of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Amniotic epithelial cells obtained from cesarean sections have been shown to express markers for neuronal, glial and progenitor cells and to differentiate into neuron-like cells in the ischemic brain of adult rats [7][8][9]. Moreover, there is evidence that amniotic fluid contains fetal mesenchymal stem cells with a multilineage differentiation potential [10][11][12][13]. In this study we extensively characterized unselected amniotic cells and tested their multilineage differentiation capacity in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…These two markers were not proposed by International Society for Cellular Therapy (ISCT; Dominici et al, 2006), however they are often used to detect MSC populations. There are many other studies of AF-MSCs, which found theses markers to be expressed in human (In't Anker et al, 2003;Tsai et al, 2004;De Coppi et al, 2007), rabbit (Steigman et al, 2009;Klein et al, 2010;DeKoninck et al, 2013;Fei et al, 2013;Kováč et al, 2016) and other species (Park et al, 2011;Chen et al, 2011;Nadri and Soleimani, 2007;Iacono et al, 2012;Choi et al, 2013). Investigators therefore use CD29 and CD44 together with some of molecular markers proposed for human MSCs by ISCT.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs are obtained from several adult mesenchymal tissue sources such as: bone marrow [8], adipose tissue [9], synovial membrane [10], periosteum [11] and dental pulp [12] as well as from non-adult tissue sources such as the fetal tissue [13], amniotic fluid [14] umbilical cord tissue (Wharton's jelly) [15] and umbilical cord blood [16].…”
Section: Mesenchymal Stromal Cells Are Known To Differentiate Into a mentioning
confidence: 99%